Analysis of the Influence of Technology Acceptance Model (TAM) Variables on User Satisfaction of the InDriver Application - Pratama, Muhammad Fandu (Information Technology and Systems, 2025)
This study aims to analyze the influence of variables within the Technology Acceptance Model (TAM) framework, namely Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BI), on the satisfaction of users of the online transportation application InDriver. TAM is a commonly used model in evaluating technology acceptance and is utilized in this research to measure the extent to which users' perceptions of the ease and benefits of using the application affect their satisfaction. Data was collected through a quantitative survey using a questionnaire with 150 respondents who are active InDriver users. The analysis method used is multiple linear regression to test the simultaneous and partial effects of each TAM variable on user satisfaction. The results show that PU and PEOU have a significant effect on attitude and intention to use, which in turn has a positive effect on user satisfaction. This finding indicates that the acceptance of technology directly affects user satisfaction in the use of digital transportation services. This research contributes to application developers and service providers in understanding the factors that influence technology-based user satisfaction.